Study on pH Effect in Process of an Entero-gastric Fiber-optic Sensor Design - Shou Wen-de; Gong Jun; Xia Rong-min; Chen Guo-ping (Sensors, 2002)
The pH effect on design of a fiber optic sensor newly developed for monitoring entero-gastric reflux is investigated. The research has been carried out by utilizing the sensor to measure characteristic absorption of bilirubin standard solution (used as a calibrator) at different pH values from about 1 to 8. The results show explicitly that the estimation error according to the calibration curves with pH <7 is significantly lower than that at alkaline pH values. Compared with the in vitro experimental data, the optimum pH range for entero-gastric reflux analysis is proposed to be between 5-6. The possible reasons for estimation error of the fiber optic sensor are given in detail.